THE INFLUENCE OF EMPLOYEE COMPETENCE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT KARTINI HOSPITAL, LEBAK REGENCY - Indah Lestari; Dina Septiana; Andri Susilo (Universitas La Tansa Mashiro, 2023)
This research aims to determine the effect of competency and work discipline on employee performance at Kartini Hospital, Lebak Regency. The method used is a quantitative method. Data collection techniques use questionnaires, observation, literature study, and documentation. The population in this study was all employees of Kartini Hospital, Lebak Regency in 2023, totaling 403 people. With a sample of 80 people obtained using the Slovin formula. The data analysis technique used uses multiple regression by going through the instrument prerequisite test stages (validity test and reliability test) and classic assumption. The results of the research show that: The Competency Variable has a positive and significant effect on Employee Performance at Kartini Hospital, Lebak Regency. Or it could be said that H1 is accepted, which means employee competency influences employee performance at Kartini Hospital, Lebak Regency. Meanwhile, the research results for the Work Discipline and its influence on employee performance, concluded that there was a positive and significant influence on employee performance at Kartini Hospital, Lebak Regency. Thus, H2 of the research is accepted, or it can be concluded that there is an influence between work discipline and the employees of Kartini Hospital, Lebak Regency. And for research regarding the influence of Competency and Work Discipline together on employee performance, it was found that there was a positive and significant influence on employee performance at Kartini Hospital, Lebak Regency. Or in other words, H3 of this research is accepted.